SISTEM KEAMANAN MOTOR MENGGUNAKAN TELEPON SELULAR BERBASISKAN KOMUNIKASI DUA ARAH - Robby Saleh; Ho Ping; Ahmad S.; Aulia U (Bina Nusantara University, 2007)
Celullar phone nowadays can be used for security system on vehicle. One of the researches that has beendone was using MMS/SMS to tell the owner of the vehicle that the vehicle was being stolen. The research purposewas to make security system on vehicle using AVR as controller and cellular phone to communicate, and the cellularphone that was on the vehicle was dialed directly to the owner informing that was being stolen. The used researchmethod was literature and experimental method. The research result indicated that the security system has responstime ± 20 seconds more faster than the system before (using MMS/SMS) that needs time 2-6 minutes.